(untitled) (Contemporary Central & East European Law, 1987)
The article presents the forms of the citizens’ participation in governing the state in socialist countries. As it is highlighted at the beginning of the article, this participation is much more intensive than in democratic countries of Europe. This is because, in socialist countries, participation is not limited to election of the citizens’ representatives every few years, but is, in different forms, realised constantly. These different forms of participation are analysed in the further part of article. In the socialist countries, participation is realised by electing the representatives who express the will of their electors and who are responsible before them, and even can be revoked before the end of their mandate. On the contrary, in democratic countries the representative is independent from the electors. In Poland there is a special notion of self-administration, which does not exist, neither in western Europe countries, nor in other socialist countries. It is embodiment of direct participation. Its realisation is provided by the activity of council of people (in countryside, cities and on the voivodship level), work councils in the enterprises, socio-professional self-administration in agriculture, cooperative self-administration and professional associations. Indirect participation is realised by social and political associations as Patriotic Movement for National Rebirth (PRON) whose broad public support justifies its broad competences (it, inter alia, organizes common consultations on proposed legal acts). Other examples are: Association of Combatants that takes care of the combatants’ rights and Environment Protection League. The exercise of state’s organs’ tasks also needs citizens’ participation, especially on the local level and in the judicial system – participation of jury in courts and the special organ judging the offences (called kolegium do spraw wykroczeń). There are also many organisations of social character, as Polish Women League, Consuments’ Federation, Social Committee against Alcoholism, Nature Protection League, National Technical Federation, Childhood Friends Society and many others. The special prerogatives are given to the Supreme Chamber of Control. Constitutional role of these institutions has been analysed in the further part of the article. Significant element of the citizens’ participation are the consultations over the projected legal acts and, existing also in other socialist countries, referendums. The results of the actions taken by the aforementioned forms of participation can be legally bounding (as the decision adopted by the majority in referendum) or may constitute only consultative opinion, for example in a form of recommendations. The last part of the article analysis the domains in which citizens’ participation may be of great importance, for example in law-making process, jurisdiction, in the executive, in social control, both on central and on local level. The conclusion is very optimistic for the future, as the citizens’ participation is constantly developing and it brings measurable effects that let the citizens feel they are part of the changes that are having place in People’s Republic of Poland.